Interactive Effects of Heat and Drought Stress on Crop Growth and Yield Formation - Abhijit Debnath,; Bashir A Alie,; Ganesh Chandra Malik,; L.Chanu Langlentombi, (Public Health, 2026)
Heat and drought stresses are among the most dominant environmental constraints limiting crop productivity worldwide, particularly under the current scenario of climate variability. While individual stress responses have been widely documented, their simultaneous occurrence presents a more severe and complex challenge to crop systems. Heat stress accelerates plant metabolism and phenological development, whereas drought stress restricts water availability, leading to reduced turgor pressure and impaired physiological functioning. When these stresses occur together, they intensify cellular damage, disrupt metabolic pathways, and significantly reduce crop yield. The combined stress adversely affects photosynthesis, nutrient uptake, reproductive development, and grain formation. It also enhances oxidative stress and alters hormonal balance, ultimately leading to premature senescence and yield loss. This review provides a comprehensive understanding of the physiological, biochemical, and molecular mechanisms underlying heat–drought interactions and discusses adaptive strategies for improving crop resilience.